The Marine Environment: Hazards, Resources and the Application of Geoethics Principles - Violante, Roberto Antonio (2018)
Oceans cover three quarters of the Earth surface and represent a fundamental component of the global climate system. Life on Earth is closely tied to the climate system and thus to the oceans. Marine regions are subjected to numerous submarine natural hazards such as earthquakes, volcanic eruptions and landslides, in many cases producing tsunamis that threaten coastal areas and many onshore and offshore man-made facilities. On the other hand, as society and technological needs progressively increase, the impact of human activities on coastal and deep waters become more severe, with consequences that include global warming and sea-level rise, coastal erosion, pollution, ocean acidification, damage to marine resources and ecosystem degradation. Nevertheless, humankind seems not to be adequately conscious about the different kind of hazards threatening the marine environment. The challenge for marine geoscientists is to be conscious of the geoethical compromise in order to alert society, industries and policy makers about the needs to minimize the risks of natural and human impacts in the ocean system.